Integrated nutrient management on growth, yield and quality of paprika alike chillies (Capsicum annuum L.) - T J Zachariah, N K Leela, K N Shiva, V Srinivasan, (Journal of Spices and Aromatic Crops, 2015)
The experiment was conducted for two seasons to study the effect of organic nutrient sources and inorganic sources of nutrients combined with biofertilizers on growth, yield and quality of paprika alike chillies (indigenous germplasm of paprika). The results revealed that application of vermicompost (250 g plant-1) combined with neem cake (100 g plant-1) recorded higher growth parameters, yield and quality attributes, which was comparable with inorganic fertilizers at the recommended levels. Under integrated nutrient management, application of 75% N (8 g plant-1) + Azospirillum spp. (5 g plant-1) + 75% P (1.7 g plant-1) + Phosphobacteria (5 g plant-1) + 100% K (2.5 g plant-1) improved the growth, yield and quality parameters of paprika alike chillies as compared to recommended NPK through fertilizers indicating a saving 25% of both inorganic N and P through biofertilizers.